Phylogeny of the infectious hematopoietic necrosis virus in European aquaculture. - Michael Cieslak; Thomas Wahli; Nicolas Diserens; Olga L M Haenen; Heike Schütze (PLoS ONE)
Infectious hematopoietic necrosis (IHN)-a highly lethal infectious salmonid disease-has caused substantial economic losses in the European production of rainbow trout (Oncorhynchus mykiss) since the late 1980s. The causal agent of IHN is the IHN virus (IHNV) introduced from overseas. However, until today, its phylogeographic spread in Europe remains poorly understood. We therefore sought to elucidate this unresolved topic by using the largest ever compiled dataset of European IHNV isolates (E isolates) (193 GenBank E isolates and 100 isolates from this study) for the complete glycoprotein (G) gene sequence. Our results clearly revealed that the active trout trade has left its traces in the E phylogeny. For example, the spread by trade of IHNV-infected trout was apparently the cause for the exposure of the E lineage to different local scenarios of selection and genetic drift, and therefore has led to the split of this lineage into various subordinated lineages. Accordingly, we also found evidence for E isolates being mixed Europe-wide by cross-border introduction events. Moreover, there were indications that this propagation of the E lineage within Europe corresponded with an extensive and rapid spread event, already during or shortly after its formation. Finally, in accordance with the high substitution rate of IHNV determined by previous studies, our dataset indicates that the mean period of occurrence of a single E haplotype is typically not longer than one calendar year.